Cultural Heritage and the Challenge of Sustainability. - Barthel-Bouchier, Diane (Left Coast Press, 2012)
'For cultural and heritage institutions around the world, sustainability is the major challenge of the twenty-first century. In the first major work to analyze this critical issue, Barthel-Bouchier argues that programmatic commitments to sustainability arose both from direct environmental threats to tangible and intangible heritage, and from social and economic contradictions as heritage developed into a truly global organizational field. Drawing on extensive fieldwork and interviews over many years, as well as detailed coverage of primary documents and secondary literature, she examines.